2019
DOI: 10.1021/acsbiomaterials.9b00895
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Assessment of Healing and Effectiveness of a Foam-Based Peripheral Occlusion Device

Abstract: The IMPEDE Embolization Plug is a catheter-delivered vascular occlusion device that utilizes a porous shape memory polymer foam as a scaffold for thrombus formation and distal coils to anchor the device within the vessel. In this study, we investigated the biological response of porcine arteries to the IMPEDE device by assessing the extent of healing and overall effectiveness in occluding the vessel at 30, 60, and 90 days. Compared to control devices (Amplatzer Vascular Plug and Nester Embolization Coils), the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 30 publications
0
55
0
Order By: Relevance
“…Near complete degradation was observed in vivo in rat subcutaneous and rabbit intramuscular implants at 180 days." Longer-term follow-up will show longer-term clinical results, however preclinical work demonstrated the conversion of thrombus to mature collagenous connective tissue as the polymeric scaffold degrades (Jessen et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Near complete degradation was observed in vivo in rat subcutaneous and rabbit intramuscular implants at 180 days." Longer-term follow-up will show longer-term clinical results, however preclinical work demonstrated the conversion of thrombus to mature collagenous connective tissue as the polymeric scaffold degrades (Jessen et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The polymer fabrication and physical properties have previously been described (Landsman et al 2016 ). Preclinical work characterised cellular infiltration into the shape memory polymer scaffold and conversion of thrombus to mature collagenous connective tissue over time (Jessen et al 2020 ). Furthermore, preclinical work suggests shape memory polymer-based devices support an advanced state of healing, within a designated timeframe, compared to other commonly used vessel embolisation devices (Jessen et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the device is deployed into the warm and aqueous environment of a blood vessel, the polymer recovers, or remembers, its original shape and self-expands. The porous nature of the expanded vascular plug supports the acute formation of thrombus throughout its structure and preclinical work has demonstrated that increased cellular infiltration leads to advanced healing of the initial thrombus to mature collagenous connective tissue when compared to other common embolic devices (Jessen et al 2020).…”
Section: Introductionmentioning
confidence: 98%
“…Preclinical work characterised cellular in ltration into the shape memory polymer scaffold and conversion of thrombus to mature collagenous connective tissue over time (Jessen et al, 2020). Furthermore, preclinical work suggests shape memory polymerbased devices support an advanced state of healing, within a designated timeframe, compared to other commonly used vessel embolisation devices (Jessen et al, 2020). Following CE marking of the devices, the manufacturer established a post market study to collect data on their routine clinical use.…”
Section: Introductionmentioning
confidence: 99%